The relationship between axial length/corneal radius of curvature ratio and stress–strain index in myopic eyeballs: Using Corvis ST tonometry - Chu, Zhe; Ren, Qi; Chen, Meizhen; Cheng, Lu; Cheng, Hao; Cui, Wei; Bi, Wenjiao; Wu, Jie (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: This study aimed to investigate the correlation of Axial Length/Corneal Radius of Curvature Ratio with Stress-Strain Index. Methods: Retrospective analysis was conducted to compare the right eyes of those with high myopia (HM, n = 132; age, 10 to 48 years) with those without high myopia (NHM, n = 135; age, 7 to 48 years), where the baseline axial length, corneal radius of curvature ratio, and central corneal thickness were analyzed, the differences in two groups were compared and the relationship of axial length, axial length/corneal radius of curvature ratio with Stress-Strain Index were explored. Results: Compared with AL<26mm, SSI was significantly decreased when AL≥26mm (p = 0.001), while no correlated with AL in the NHM group (r = -0.14, p = 0.12) or HM group (r = -0.09, p = 0.32). AL/CR was significantly associated with SSI in both the NHM (r = -0.4, p < 0.001) and HM (r = -0.18, p = 0.04) groups. In the NHM group, AL/CR was significantly associated with SSI (unstandardized beta = -0.514, se = 0.109, p < 0.001) with adjustment of age and gender. Additionally, a significant association of SSI with AL/CR was also found after adjusting for age and gender (unstandardized beta = -0.258, se = 0.096, p = 0.0082) in the HM group. Conclusion: SSI showed a significant negative correlation with AL/CR in patients without high myopia and in patients with high myopia. However, SSI exhibited no decrease with the worsening of myopia, but it gradually remained stable at a low level. The findings of this study validate, to some extent, the possibility of analyzing the dynamic changes in ocular wall stiffness during the development of myopia by measuring in vivo corneal biomechanical parameters.